2018
DOI: 10.22437/bio.v4i2.6177
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of ICT-based Classwide Peer Tutoring (CWPT) Application and Motivation to Biology Education Student Creativity in ICT Learning

Abstract: Abstract. The rapid development of ICT, especially in learning, could not be parted from ICT intervention. Many benefits obtained from ICT developments, if this technology is utilized optimally in learning, there will have an impact on improving the quality of learning in particular and the quality of education in general. The lack of student knowledge and motivation for ICT technology can have an impact on students' creativity in using this technology optimally in learning. Peer tutoring can be an alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
2
1
1
Order By: Relevance
“…In the same vein, Abdulmalik and Torpev (2016) and Alemu (2020) of whom also agreed that CWPT could bring about improved performance of students. Similarly, it contradicts the findings of Anggereini, Budiarti, and Sanjaya (2018) who reported that there was no effect of the CWPT model on student creativity.…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…In the same vein, Abdulmalik and Torpev (2016) and Alemu (2020) of whom also agreed that CWPT could bring about improved performance of students. Similarly, it contradicts the findings of Anggereini, Budiarti, and Sanjaya (2018) who reported that there was no effect of the CWPT model on student creativity.…”
Section: Resultscontrasting
confidence: 78%
“…Results showed that the experimental group taught by peer tutors via CWPT performed significantly better than the control group taught by using the lecture method. Anggereini et al (2018) studied the effect of ICT-based class-wide peer tutoring (CWPT) on the creativity of biology education students in Jambi, Indonesia. Descriptive data analysis and inferential statistics of 2-ways ANOVA were employed in the study.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of the data obtained was sought and then expressed in several categories including very bad, not good, good and very good and analyzed using descriptive statistics. Descriptive data analysis is useful for knowing the interactions between these variables by calculating the distribution of frequencies, averages, and standards [38].…”
Section: Methodsmentioning
confidence: 99%
“…Berdasarkan penelitian [12], lingkungan belajar dapat dikatakan baik dengan beberapa indikator antara lain metode, kurikulum, relasi, dan disiplin sekolah. Dengan semakin berkembangnya teknologi informasi, guru juga harus semakin kreatif dan inovatif mengembangkan lingkungan belajar [17]- [19]. Oleh karena itu, lingkungan belajar yang selama ini belum berkembang, dapat ditingkatkan lagi oleh guru dan sekolah guna mencapai sikap positif khususnya dalam mata pelajaran IPA.…”
Section: Pendahuluanunclassified